An examination of the effectiveness of traps and baits as a possible means of harvesting crayfish, Cherax quadricarinatus in Sanyati Basin, Lake Kariba, Zimbabwe - L Mhlanga; L Marufu; G Mupandawana; T Nhiwatiwa (Water SA, 2020)
Although Cherax quadricarinatus is now established in Lake Kariba, there is a lack of information on the appropriate gear technology and bait for its exploitation for either management or commercial purposes. The effectiveness of three trap designs and three bait types was investigated in order to identify the best means for harvesting C. quadricarinatus in Lake Kariba. The cylindrical and rectangular traps had higher and similar CPUE, which were significantly higher than those of the Opera house trap at all sites. Trap type did not influence sex ratio. Liver, sadza and fish heads were all similarly effective as bait. Either sadza-baited cylindrical or rectangular traps can be effectively employed to either harvest crayfish in order to maintain a low population, thereby mitigating potential adverse impacts, or for commercial purposes. This should be corroborated with monitoring and further research.